2018
DOI: 10.1371/journal.pone.0198598
|View full text |Cite
|
Sign up to set email alerts
|

Food acquisition methods and correlates of food insecurity in adults on probation in Rhode Island

Abstract: BackgroundIndividuals under community corrections supervision may be at increased risk for food insecurity because they face challenges similar to other marginalized populations, such as people experiencing housing instability or substance users. The prevalence of food insecurity and its correlates have not been studied in the community corrections population.MethodsWe conducted a cross-sectional study in 2016, surveying 304 probationers in Rhode Island to estimate the prevalence of food insecurity, identify f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Four depression studies and two sleep studies had overlapping data; the most recent study in pairs of overlapping studies was kept. [39][40][41][42][43][44] Most studies had a wide age range, while only a few studies provided data on agespecific groups: five studies on 50+-year-old adults and six on Figure 1 Flow diagram for the search and study selection processes.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four depression studies and two sleep studies had overlapping data; the most recent study in pairs of overlapping studies was kept. [39][40][41][42][43][44] Most studies had a wide age range, while only a few studies provided data on agespecific groups: five studies on 50+-year-old adults and six on Figure 1 Flow diagram for the search and study selection processes.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…2), the OR was 2.74 [95% CI 2.52-2.97, Q(df = 41) = 69, I 2 = 40%]. 40,41, One study was divided into two groups for the meta-analysis. 76 Thirteen studies (n = 5837) ( Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…What limited research has been conducted with people on probation has found that housing is also a priority issue among this groups. In a survey of people on probation in Rhode Island ( n = 304), more than 20% reported being homeless (Dong et al, 2018a; see, also, Dong et al, 2018b). We know of no study to date that has captured living situation or housing instability among people on probation.…”
Section: Housing Circumstances Among the Justice-involvedmentioning
confidence: 99%
“…Dong et al also examined Rhode Island using GIS as a tool [28]. However, their focus was on food insecurity among adults who are on probation.…”
Section: Discussionmentioning
confidence: 99%